Johnny Cash : the life in lyrics - Cash, Johnny; Stielper, Mark (Voracious/ Little, Brown and Company, 2023)
"Johnny Cash is one of the most beloved and influential country-music stars of all time, having composed more than six hundred songs and sold more than ninety million records. He received twenty-nine gold, platinum, and multiplatinum awards for his recordings and has been inducted into the Grammy Hall of Fame, the Rock & Roll Hall of Fame, the Country Music Hall of Fame, and the Hollywood Walk of Fame. This is the first time Cash's fifty years of songwriting have been collected anywhere; this book includes the lyrics to 125 songs and the stories behind them. Perhaps more than any other American artist, he spoke to the soul of the nation as well as to the triumphs and challenges of his own life. These pages explore Cash's range as a poet and storyteller, taking readers from his early life and first successes through periods of personal challenge, activism, and faith. The result is a profound understanding of Johnny Cash as a man and an artist, as well as the American story he helped shape" --